Lessons from the Late Erich Fromm: Novel Ideas for Social Work Theory and Practice That Were Ahead of Their Time - St. Jean, Sean (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2016)
The field of social work is currently wrestling with a number of divergent theories and concepts as it seeks to discover ways of thinking about social issues, client worlds, and best practices. Yet many of those eclectically gathered theories are not aligned logically or philosophically. This has led to a disjointed, ad hoc, and disunited theoretical basis within the field that has, arguably, weakened its collective effectiveness, reputation, and impact. Erich Fromm (1900-1980), a German-born psychoanalyst and philosopher, offers a number of theoretical ideas, stances, and directions that may improve social work’s theoretical underpinnings and perhaps even provide some foundational elements useful for the creation of a unified theory of human functioning in the world. This article explores Fromm’s body of work with the intention of applying a selection of his ideas to social work theory, policy, and practice. Remedies to resolve the bifurcation of psyche-based and society-based theories are discussed. Following this is a presentation of Fromm’s concept of “social character” as well as implications for social work practice.